Multi-modem-based FHSS-drone takeover with precision spoofing - Jae Gu Kang; Byeong Cheol Choi (ETRI Journal)
Traditional radio frequency (RF)-based anti-drone technologies focus on jam-ming the command and control (C2) RF signal or global navigation satellite system (GNSS) signal of a target drone. Although these methods efficiently neutralize target drones, they may generate unintended RF collisions with other equipment and cause the drone to crash. We introduce a method for hijacking a frequency hopping spread spectrum (FHSS)-based drone through C2 signal emission for takeover and a precision spoofing signal to invalidate the owner’s transmitter signal using a multi-modem in this work. The pro-posed method simultaneously transmits C2 signals to the target drone for safe takeover and precision spoofing signals to neutralize the owner’s transmitter, thereby minimizing RF collisions with other equipment.